PELATIHAN DIVERSIFIKASI PRODUK TOGA UNTUK MENINGKATKAN KEMANDIRIAN KESEHATAN SISWA SMA - Putri, Devi Anggraini; Mawli, Rizka Efi; Nuraini, April; Ramadhania, Nurina Rizka; Alifah, Nur Fadhilatul; Kaffi, Raisha Aradea (Universitas Mataram, 2024)
TOGA diversification is to increase variety of herbal products for their quality, acceptance, and economic value. In Indonesia, TOGA, known as herbs or jamu, is not only used as traditional medicine, but also used as a health supplement to maintain body immunity. Therefore, the community service team strives to improve public health through TOGA diversification training. The targets are high school students who are members of the MPS Botany group of SMAN 1 Bangkalan. The aim of this program is to increase the health independence of targets through TOGA diversification training. The methods are divided into several steps including the preparation, implementation, namely training and workshop, and evaluation through pre- and post-tests and satisfaction surveys. The implemented diversification training has been able to improve the knowledge and skills of targets to produce TOGA made from turmeric into a variety of products including fresh drinks, instant powders, and contemporary drinks. Based on the results of data analysis, 77% of participants experienced an increase in knowledge based on an increase in post-test scores. Then, 68 and 58% of participants respectively assessed the benefits and sustainability of the program as very good. Thus, TOGA diversification training activities are recommended to be continued and developed. This program is expected to be able to improve the health independence of high school students in the future.